Home sweet home - Marzollo, Jean (USA : HarperCollins Publishers, 1997)
Illustrations and simple rhyming text ask blessing on everything on earth, from ant to tree, stream to whale, and also on moonbeans ans stars.
Keywords: Earth-Religious aspects-Juvenile literature; Children-Prayer-books and devotional-English; Prayers; Religious aspects